ANALISIS FUNDAMENTAL TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI - SIGIT SANJAYA; WINDA AFRIYENIS (Maqdis: Jurnal Kajian Ekonomi Islam, 2018)
This research aims to discover the effect of 1) Return on Assets (ROA) to stock price 2) Return on Equity (ROE) to stock price 3) Debt to Equity Ratio (DER) to stock price 4) Earning Per Share (EPS) to stock price 5) Price Earning Ratio (PER) to stock price 6) Book Value Per Share to stock price 7) Return on Investment to stock price 8) Price to book value (PBV) to stock price. The research population is sharia consumption sector listed in Indonesia Stock Exchange (IDX). Samples are drawn by purposive sampling method. The total sample in this research is 29 companies. The data sourced is secondary data. Data analysis technique using multiple regressions. The results showed 1) Return on Assets (ROA) have a significant effect on stock prices 2) Return on Equity (ROE) has a significant effect on stock prices 3) Debt to Equity (DER) has no significant effect on stock prices 4) Earning per Share (EPS) has a significant effect on stock prices 5) Price Earning Ratio (PER) has a significant effect on stock prices 6) Book Value Per Share (BVS) has no significant effect on stock price 7) Return on Investment (ROI) has no significant effect on stock prices 8) Price to Book Value (PBV) has a significant effect on stock prices.